A study for the protection and utilization of the Huzhou new rural tourism landscape resources based on a Rural Residence Image System (RRIS） - Q. Yang; K. Sheng (International Association of Lowland Technology, 2018)
The utilization of rural tourism landscape resources is an important aspect of new rural development. How to effectively balance the protection and construction of rural landscape resources has recently become the focus of research studies. By taking Huzhou City as an example, this study summarized the problems in the current based on an investigation. Then, it reconstructed the development goals of the tourism landscape resources in the rural areas, introduced an innovation idea of a “Rural Residence Image System”, and established a new development model based on “nature, entirety, and sharing”. A Rural Residence Image System is in fact the sum of the tangible and intangible cultural landscape resources, which continue the existing rural cultural traditions. Also, it is the exploration and practice of innovation concepts regarding the in-the-field planning science and architecture of rural tourism landscape development. On this basis, countermeasures and suggestions were formulated for the protection and utilization of resources.